Internet addiction and aggression in high school students from Peru - Matalinares Calvet, María (2013)
Present study aimed to identify the relationship between aggression and Internet addiction. Sample consisted of 2225 high school students, aged 13 to 19, from third to fifth years. They came from 13 cities representing coast, highlands and jungle Peruvian regions. A comparative and correlational descriptive study design was used and the Buss & Perry Hostility Inventory (1992) and the Internet Addiction Test by K. Young were the instruments applied, previously adapted to national reality. Results show positive relationship between Internet addiction and aggression and among all components of both research variables. Men tend to be more physically and verbally aggressive while women tend to experience more anger and hostility. Male gender, living on the coast region of Peru, easier access to Internet without supervision, being between 15 and 16 years old and having high aggression scores were risk- factors found for developing addiction to Internet. Implications of the study are discussed.